Ascaris lumbrocoides in the Right Maxillary Sinus-a rare case - Saha, Kanu Lal; Rashid, Md Sajibur; Jamtsho, Sonam; Talukder, Debesh Chandra (Journal of Dhaka Medical College, 2020)
Introduction: Sinusitis is fairly a common condition in an Otolaryngology clinic.However sinusitis due to Ascaris lumbrocoides obstructing the maxillary ostium is a very rare case. Objective: To report a very rare case of round worm in the Right Maxillary sinus. Case report: A nine year old girl presented with right nasal blockage and dull aching pain over the right maxilla and foul smelling discharge from the right nostril for a week duration. Examination revealed a cord like structure in the right nostril which was very painful on manipulation. Examination under generl anesthesia revealed a 15 cm long dead Ascaris lumbrocoides in the right nostril emerging from the right maxillary sinus obstructing its ostium. After removal of the round worm, patient and the immediate family members were treated with Albendazole. Conclusion: In rare occasions, particularly in underdeveloped countries, clinicains should be midful that round worms can be a cause of sinusitis. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 126-128